Pengendalian dan Pemantauan Mesin Tetas Telur Ayam Menggunakan XBee - Noveri Lysbetti Marpaung; Dedy Nurahmadin; Rahyul Amri; Edy Ervianto; Nurhalim Nurhalim (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Chicken eggs can be hatched in two ways namely, incubated by a hen directly and by using a created egg hatching machine. The egg hatching machine replaces role of the hen in egg incubation process. Checking hatching machines manually by checking the stabilities of temperature and humidity in the hatching room one by one, cause temperature and humidity instabilities to be a problem, so eggs are failed to hatch. This problem can be solved by using monitoring and pengendalian system of a hatching machine uses XBee Tansmitter and XBee Receiver in 5meters,10meters,20meters indoor. XBee Tansmitter is on incubation machine connected to Arduino-Uno-ATMega328. DHT22-Sensor detects temperature and humidity readings. XBee Receiver is on user’s space connected to Arduino-Uno-ATMega328. SD Card saves temperature and humidity data. Temperature and humidity monitoring in 24 days since eggs were put into hatching machine in 37.80C–38.70C temperature and humidity of 50%-60%. After 3 days eggs put into machine, Servo Motor turns back 1800 Egg’s rack within eggs every 3 hours, until eggs hatch. Eggs hatched since 19th day. Total of hatching eggs are 19 from 23. Can be concluded that the research work well because hatching eggs well reached 82.61%.